The Influence of Telenursingagainst Adherence to Anti TB Treatment toward Tuberculosis Patient in BIMA City (Medico Legal Update, 2021)
Tuberculosis (TB) is an infectious disease that is caused by Mycobacterium tuberculosis, which attacksvarious organs, especially lungs. This disease must be treated immediately before it causes complicationseven death. The number of TB cases in Indonesia was 420,994 cases in 2017. Lack of adherence against TBtreatment still becomes an obstacle of global health, and mobile phone-based interventions have potentialto solve this problem. Furthermore, this research aimed at investigating the influence of telenursing againstadherence to anti-TB treatment toward patient with tuberculosis. This research was conducted in Bima City,West Nusa Tenggara Province, Indonesia which consisted of 3 (three) Public Health Centers. Method of thisresearch was experimental anddesign in this research used quasi experimental design (One group PretestPosttest Design). Moreover, results of this research showed that TB respondents before being treatedbytelenursing who were in category of moderate adherence were 14 respondents (23.3%), meanwhile, incategory of poor adherence were 46 respondents (76.7%). After being treatedby telenursing, TB respondentswho were in category of high adherence were 60 respondents (100%). Test through SPSS was obtained asignificant result which was 0.001 for intervention with a significance level of 0.05. Because p value was